2015
DOI: 10.1080/00913367.2015.1085820
|View full text |Cite
|
Sign up to set email alerts
|

Redressing the Sleeper Effect: Evidence for the Favorable Persuasive Impact of Discounting Information Over Time in a Contemporary Advertising Context

Abstract: (2016) Redressing the sleeper effect: evidence for the favorable persuasive impact of discounting information over time in a contemporary advertising context. Journal of Advertising Research, 45 (1). pp. [19][20][21][22][23][24][25] This version is available from Sussex Research Online: http://sro.sussex.ac.uk/68656/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 25 publications
(61 reference statements)
2
18
1
1
Order By: Relevance
“…That could be explained with the fact that the media brand was presented before the message, while the user comments were presented after the message. According to the differential decay hypothesis and based on earlier research (Foos et al, 2016;Gruder et al, 1978;Kumkale and Albarracín, 2004), a sleeper effect is more likely to occur when the discounting cue is presented after the message.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That could be explained with the fact that the media brand was presented before the message, while the user comments were presented after the message. According to the differential decay hypothesis and based on earlier research (Foos et al, 2016;Gruder et al, 1978;Kumkale and Albarracín, 2004), a sleeper effect is more likely to occur when the discounting cue is presented after the message.…”
Section: Discussionmentioning
confidence: 99%
“…Although the impacts of the two communications are equal initially after exposure, the influence of the discounting cue decays more rapidly than the influence of the message arguments (Pratkanis et al, 1988). Several other studies have confirmed that a sleeper effect is more likely to occur when the discounting cue is presented after the message (Foos et al, 2016;Gruder et al, 1978;Kumkale and Albarracín, 2004).…”
Section: Differential Decay Hypothesismentioning
confidence: 96%
See 2 more Smart Citations
“…Hal ini biasa dikenal dengan istilah sleeper effect. Sleeper effect semakin mudah terjadi jika didukung dengan kondisi yang sangat elaboratif dan berulang (Foos et al, 2016). Peningkatan persuasi juga bergantung pada kualitas pesan dan kredibilitas komunikatornya (Albarracín et al, 2017).…”
Section: Konsep Ideal Yang Semuunclassified